Politik Hukum Pembatasan Penggunaan Kantong Plastik Sekali Pakai dalam Produk Hukum Daerah - Siregar, Rajacia Angeline; Artina, Dessy; Diana, Ledy (PATTIMURA Legal Journal, 2024)
Introduction: Waste management in Pekanbaru City has received national attention because it is not handled properly. Pekanbaru City can produce 42 tons of plastic waste a day, which is around 20 percent of the total daily waste production. Purposes of the Research: To understand the legal politics and ideal concept of regulating restrictions on the use of single-use plastic bags in regional legal products in the city of Pekanbaru. Methods of the Research: The type of research used is normative legal research, namely using library research to search for data. Results Originality of the Research: The research results show that Article 7 paragraph (1) of Pekanbaru Mayor Regulation Number 6 of 2023 concerning Reducing the Use of Plastic Bags is still not a solution in overcoming the problem of plastic waste in the city of Pekanbaru.